Detection and genome characterization of iPotato virus/i Y isolates infecting potato (iSolanum tuberosum/i L.) in La Union (Antioquia, Colombia) (2016)
Potato virus Y (PVY) is one of the most severe viruses affecting the production of potato (Solanum tuberosum) in the world. This study presents a detailed molecular analysis using nextgeneration sequencing (NGS), IC-RT-qPCR and RT-PCR on the PVY isolates infecting seed-tubers and foliage of potato plants cv. Diacol-Capiro in La Union (Antioquia, Colombia). Analysis of incidence by IC-RT-qPCR in 15 random leaf samples of three cultivation plots and fifteen sprouting tuber eye-buds reveal infection levels between 13.4 and 80%; a higher incidence of 86.7% was observed in seed-tuber samples with threshold cycle (Ct) values as low as 24.3. Genome assembly from a bulk of foliage samples resulted in a consensus PVY genome (PVY_LaUnionF) of 9,702 nt and 399 polymorphic sites within the polyprotein ORF; while the assembled genome from sprouts of tubers has 9,704 nt (PVY_LaUnionT) and contained only six polymorphic nucleotide sites. Phylogenetic analysis demonstrates that the PVY isolates from leaf samples are in the recombinant PVYNTN group (sequence identity 99%); while those from tuber sprouts are in the PVYN/NTN group with identities above 95%. Sanger sequencing of viral capsid suggests the presence of a third variant related to PVYO, a prevalent strain reported in potato fields worldwide.